CALCULATION OF THE VARIABLE COST OF WELDING IN API TANK - Córdova Procel, Juan Roberto; Miño Cascante, Gloria Elizabeth; Vargas Guambo, Blanca Irene; Vega Cortez, Paúl Oswaldo (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
Managing costs in the area of welding of metalworking products is of great importance, as cited by various authors, specifically from the management point of view for a timely and correct decision making when budgeting for the sale of this type of products. This research of the descriptive type with deductive method was based on data obtained in the construction of twenty oil storage tanks in eastern Ecuador, and aimed to find a mathematical model that allows professionals to manage costs and budgets in the area of metalworking, have a reliable tool for calculating variable welding costs and the hours of labor that this construction process implies. In the market there are multiple options to obtain this data, one of them is the handling of catalogs published by welding manufacturers, however, they can be considered ideal while those obtained in this work are the result of empirical data, where It obtained a margin of error of up to 3% when comparing budgeted costs, that is, before execution versus actual costs.